2018
DOI: 10.1021/acsmedchemlett.8b00344
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Quinoline-Based RIP2 Kinase Inhibitors with an Improved Therapeutic Index to the hERG Ion Channel

Abstract: RIP2 kinase was recently identified as a therapeutic target for a variety of autoimmune diseases. We have reported previously a selective 4-aminoquinoline-based RIP2 inhibitor GSK583 and demonstrated its effectiveness in blocking downstream NOD2 signaling in cellular models, rodent in vivo models, and human ex vivo disease models. While this tool compound was valuable in validating the biological pathway, it suffered from activity at the hERG ion channel and a poor PK/PD profile thereby limiting progression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…Recently, groups including ours have reported that small molecule RIP2 inhibitors block proinflammatory signaling and reduce inflammation in preclinical models. Together, these data support the notion that the NOD/RIP2 signaling pathways likely play a significant role in the pathogenesis of inflammatory diseases and that specific targeting of this pathway may have broad therapeutic value.…”
supporting
confidence: 61%
“…Recently, groups including ours have reported that small molecule RIP2 inhibitors block proinflammatory signaling and reduce inflammation in preclinical models. Together, these data support the notion that the NOD/RIP2 signaling pathways likely play a significant role in the pathogenesis of inflammatory diseases and that specific targeting of this pathway may have broad therapeutic value.…”
supporting
confidence: 61%
“…Many of these reports have presented in vitro studies that have demonstrated the importance of the ternary complex between the target protein, the PROTAC, and the E3 ligase complex in determining not only the degradation efficiency, but also introducing greater degradation selectivity as compared to the native binding selectivity of the target binding moiety of the corresponding PROTAC [33][34][35][36] . In the current work, we began with a highly potent and selective RIPK2 inhibitors already available as a result of previous RIPK2 lead optimization efforts 25,37 , and we were able to quickly demonstrate effective degradation of the target protein with PROTACs based on these inhibitors. It is noteworthy that the highly potent cellular degradation of RIPK2 by PROTAC 2 (pDC 50 = 9.4 ± 0.1) is achieved from a less potent biochemical RIPK2 IC 50 of 10 nM.…”
Section: Discussionmentioning
confidence: 99%
“…This work is the first to demonstrate the efficacy and modulatory activity of a RIP2-targeting compound using a clinically relevant model of allergic asthma. Numerous inhibitors have both been discovered and developed for modulation of RIP2 activity (23,(41)(42)(43)(44)(45)(46)(47)(48)(49). The RIP2 inhibitor used in this study, GSK583, has been reported to be highly selective and exhibits strong potency even in vivo (23,45).…”
Section: Discussionmentioning
confidence: 99%